How Do We Treat Pregnancy-Related Venous Thromboembolism? - Linnemann, Birgit; Seelbach-Goebel, Birgit; Heimerl, Susanne; Hart, Christina (Hämostaseologie, 2020)
Venous thromboembolism (VTE) is a major cause of maternal morbidity and mortality during pregnancy and the postpartum period. Due to a lack of adequate study data, therapeutic strategies for pregnancy-related VTE are deduced from observational studies and extrapolated from recommendations for nonpregnant patients. Because heparins do not cross the placenta, weight-adjusted therapeutic-dose low-molecular-weight heparins (LMWHs) are the anticoagulant treatment of choice in cases of VTE during pregnancy. Once- and twice-daily dosing regimens are suitable. There is no evidence that measurement of factor Xa activities and consecutive LMWH dose adjustments improve clinical outcomes. There is no support for the routine use of vitamin K antagonists, direct oral thrombin or factor Xa inhibitors, fondaparinux, or danaparoid in uncomplicated pregnancy-related VTE. Management of delivery deserves special attention, and treatment strategies depend on the time interval between the diagnosis of acute VTE and the expected delivery date. In lactating women, an overlapping switch from LMWH to warfarin is possible. Anticoagulation should be continued for at least 6 weeks postpartum or for a minimum period of 3 months.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; heparin; pregnancy; postpartum